PENGEMBANGAN LEMBAR KERJA SISWA LISTRIK DINAMIS BERBASIS POE (PREDICT-OBSERVE-EXPLAIN) UNTUK MENINGKATKAN PENALARAN DAN PEMAHAMAN KONSEP SISWA - Falah, Syarifatul; Hartono, Hartono; Yulianti, Ian (UPEJ Unnes Physics Education Journal, 2017)
The purposes of this study are to produce a worksheet with POE characteristics, how its properness, and how students’ reasoning and understanding improvement after its application. Research and Development (R&D) method with Pre-experimental One-Group Pretest-Posttest Design is used in this study. The procedures are: potential and problem, information collecting, product design, product validation, revision, small scale trial, revision, application. The properness test uses properness questionnaire. The data of students’ reasoning and conceptual understanding is taken from pretest and posttest. The properness test results indicate that Electrodynamics worksheet based on POE strategy is very proper as a teaching-material. Students’ reasoning and concept understanding improvement are in medium criteria after its application.